PENGARUH PENDIDIKAN KESEHATAN MEDIA VIDEO TERHADAP SIKAP MELAKUKAN SADARI PADA WANITA USIA SUBUR DI BANJAR MAMBANG GEDE SELEMADEG TIMUR - Desak Made Firsia Sastra Putri (JURNAL MEDIKA USADA, 2022)
Background : Breast cancer is the main killer of women, 1 in 8 cases of breast cancer are found in women under 45 years of age. From the interviews, eight people had heard of BSE but had never done on a regular basis, the other two people did not know about BSE. Objective: This study aims to determine the effect of BSE health education with video on the attitude of doing BSE in women of childbearing age in Banjar Mambang Gede, Selemadeg Timur. Methods: Quantitative research using a pre-experimental design one group pretest posttest. The number of samples is 38 people using purposive sampling. The research instrument used a questionnaire. The statistical test used was the Wilcoxon test with a 95% confidence level and p<0.05. Results: Before giving the intervention three respondents (7.9%) had a positive attitude. After giving the intervention 18 respondents (47.4%) had a positive attitude. Wilcoxon analysis test obtained a value of = 0.00 which means that there is a significant effect of BSE health education with video on the attitude of doing BSE in women of childbearing age. Conclusion: There is an effect of BSE health education with video on the attitude of doing BSE in women of childbearing age